International Law on Cultural Heritage: The Benefit of Updating the International Community’s Classification of Perpetrators of Cultural Heritage Looting and Destruction - Agelarakis, Panayotis (Technical Annals, 2023)
Since the Hague Convention for the Protection of Cultural Property in the Event of Armed Conflict of 1954 (Hague Convention), the international community has committed to the protection and preservation of cultural heritage. Remaining one of the most central dedicated pieces of International Law on cultural heritage, the lack of updated International Law on the concept finding similar levels of success in obligating states and generating new norms regarding cultural heritage has exposed the age of the convention. Absent from the Hague Convention is a proper classification of perpetrators of cultural heritage crimes. In the past, perpetrators have been convicted of war crimes and crimes against humanity, yet convictions were linked with other egregious acts. The 2016 International Criminal Court Al-Mahdi Case and United Nations Security Council Resolution 2347 both declaring perpetrators of cultural heritage crimes are war criminals was a significant advancement, yet limited, particularly as war crimes cannot occur during times of peace and the difficulty of International Law’s application of rules of war during non-international conflict. This research project argues that purposeful looting and destruction of cultural heritage can and ought to be considered a crime against humanity. Through this approach, a greater number of cultural heritage crime perpetrators can be held accountable. By educating civilians on the importance of cultural heritage and previous state commitments, increased pressure can be placed on governments to abide by previous international commitments, hold states accountable for actions or inactions, and facilitate further transdisciplinary efforts for cultural heritage protection and preservation.